The role of polymorphism of hemostatic system genes in the risk assessment of the surgical treatment of chronic thromboembolic pulmonary hypertension - I. Yu. Loginova; O. V. Kamenskaya; A. M. Chernyavskij; A. N. Shilova; V. V. Lomivorotov (Российский кардиологический журнал)
Aim. To assess polymorphisms of the hemostatic system genes in patients with chronic thromboembolic pulmonary hypertension (CTEPH) and their influence on the results of thrombendarterectomy from the branches of the pulmonary artery.Material and methods. The study included 70 people with verified CTEPH who underwent thrombendarterectomy from the branches of the pulmonary artery. We studied the prevalence of polymorphisms of the hemostatic system genes (F2: 20210 G>A; F5: 1691 G>A (Arg506Gln); F7: 10976 G>A (Arg353Gln); F13: G>T (Val34Leu); FGB: 455 G>A; ITGA2: 807 C>T (Phe224Phe); ITGB3: 1565 T>C (Leu33Pro); SERPINE1 (PAI-1): 675 5G>4G) and their relationship with the immediate and long-term results of surgical treatment.Results. One or several polymorphisms of the hemostasis system genes were registrated in 98% of cases in the group with CTEPH. The most common polymorphism of the SERPINE1 (PAI-1) gene was 675 5G>4G (in 80% of cases). Mutation of the F2 gene: 20210 G>A was noted in 14% of patients, F5: 1691 G>A (Arg506Gln) - 13%, F7: 10976 G>A (Arg353Gln) - 11%, F13: G> T (Val34Leu) - 34 %, FGB: 455 G> A - 35%, ITGA2: 807 C>T (Phe224Phe) - 48%, ITGB3: 1565 T>C (Leu33Pro) - 24%. The only factor influencing the results of surgical treatment was the polymorphism of the prothrombin gene (20210 G>A), which showed a high predictive value in assessing the risk of respiratory failure in the early postoperative period of thrombendarterectomy from the branches of the pulmonary artery (OR 3,5 (1,7-18,8) p=0,041). Other genetic disorders of the hemostatic system did not show significant associations with the outcome of surgical treatment.Conclusion. We showed the relationship between the presence of prothrombin gene polymorphism (20210 G>A) and the increased risk of respiratory failure in the early postoperative period of thromboendarterectomy from the branches of the pulmonary artery. Other genetic disorders of the hemostatic system and their carriage did not show significant associations with the outcome of surgical treatment.